Multilevel Simulation of Heterogeneous Reconfigurable Platforms - Damien Picard; Loic Lagadec (International Journal of Reconfigurable Computing)
This paper presents a general system-level simulation and testing methodology for reconfigurable System-on-Chips, starting from behavioral specifications of system activities to multilevel simulations of accelerated tasks running on the reconfigurable circuit. The system is based on a common objectoriented environment that offers valuable debugging and probing facilities as well as integrated testing features. Our system brings these benefits to the hardware simulation, while enforcing validation through characterization tests and interoperability through on-demand mainstream tools connections. This framework has been partially developed in the scope of the EU Morpheus project and is used to validate our contribution to the spatial design task.